STRATEGI PEMBELAJARAN QIRÃ’AT AL-QUR’ÃN - Rahmat Hidayat (The Faculty of Tarbiyah and Teacher Training associated with PSPII, 2012)
This study aims to determine the effect of peer tutors learning strategies and achievement motivation on learning outcomes of students of class VIII subjects Qirâ’at al-Qur’ân. This research used a 2x2 factorial experimental design and was performed in MTs Ex PGA Univa Project Field with sample of 48 students. The results show: 1) The students who learn Qirâ’at al-Qur’ân through peer tutoring learning strategy is higher than those who learn through expository teaching strategies in MTs Ex PGA Univa Medan Project, 2) learning outcomes of Qirâ’at al-Qur’ân of students who have high achievement motivation with learning strategy peer tutors is higher than expository teaching strategy in MTs Ex PGA Univa Medan Project, 3) learning outcomes of Qirâ’at al-Qur’ân of students who have low achievement motivation and learning strategy is lower than the peer tutor learning strategies Ex MTs expository PGA Univa Medan Project, 4) There is interaction between learning strategies and achievement motivation on learning outcomes Qira'at al-Qur'an of student MTs Ex PGA Univa field Project.